S94 Tumour Necrosis Factor receptor 1 inhibition using a novel inhaled human antibody reduces inflammation in a human model of lung injury induced by inhaled lipopolysaccharide; a randomised placebo-controlled clinical trial. (14th November 2013) - O'Kane, CM; Bayliffe, A; Serone, A; Bareille, P; Smith, S; Hamid, U; Brown, V; Wright, T; Chen, Y; Wilson, R; Elborn, JS; McAuley, DF
Abstract : Introduction and Objectives: Tumour Necrosis Factor receptor 1 (TNFR1) transduces the pro-inflammatory activity of TNF-α, whereas signalling through TNFR2 may contribute to tissue repair. Attenuation of TNFR1 signalling, whilst simultaneously preserving the effects of TNFR2 signalling, may be beneficial in management of acute lung injury (ALI). GSK1995057 is a novel, fully human antibody fragment (domain antibody) that selectively binds TNFR1 and antagonises signalling of TNF-α via TNFR1. The aim of this clinical study was to investigate the effect of nebulised GSK1995057 on pulmonary and systemic inflammation and cell injury in an in vivo human model of lung injury induced by inhaled lipopolysaccharide (LPS). Methods: Healthy subjects were enrolled in a double-blind, placebo-controlled study and randomised to nebulised GSK1995057 or placebo (1:1) administered 1 hour prior to LPS inhalation. Measurements were performed in bronchoalveolar lavage (BAL) fluid obtained at 6 hours after LPS challenge (7 hours after dosing) and in serum obtained over 24 hours post dosing of GSK1995057. The primary endpoint was BAL neutrophil count at 6 hours post LPS exposure. Data are geometric mean (95% CI). Results: Thirty-seven healthy subjects were enrolled. One subject in the placebo group was excluded from the analysis of BAL markers as the BAL was technically poor. Pre-treatment with inhaled GSK1995057 significantly reduced pulmonary and systemic markers of inflammation. In addition, there was a reduction in pulmonary vWF reflecting reduced endothelial cell injury/activation (Table 1 ). The prevalence of LPS-induced clinical symptoms (e.g. fever, nausea) was also lower in GSK1995057 treated subjects compared with placebo treated subjects. There were no serious adverse events related to study drug. Conclusion: This is the first report that inhalation of a novel human antibody fragment directed against the TNFR1 receptor attenuates mechanisms implicated in the pathophysiology of ALI. GSK1995057 may be a potential therapy for ALI. ClinicalTrials.gov identifier: NCT01587807 . This work was funded by GlaxoSmithKline.